PENGATURAN KEDUDUKAN SAHABAT PENGADILAN DALAM SISTEM PERADILAN PIDANA INDONESIA (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
A court decision is decided by a panel of judges, in accordance with the contents of Article 5 paragraph (1) of Law Number 48 of 2009 concerning Judicial Power if deciding on a case the judge is obliged to explore, follow and understand the legal values and the sense of justice that live in society. Justice that lives in community life becomes an opening for a person, group of people or organization that does not act as a party in a case but has an interest in or has an interest in submitting the amicus curiae. Amicus curiae is a term in the legal tradition which means “friend of the court”. Amicus curiae's statement is therefore a written statement from a third party expressing his opinion on certain matters in an ongoing legal process. Amicus curiae is only limited to providing opinion, and not fighting. Amicus curiae's position should be clearly explained in the law, because amicus curiae can help judges decide a case appropriately and fairly.This legal research is a normative legal research. Normative legal research is legal research conducted by examining library materials or secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. Normative legal research is also called doctrinal legal research, also referred to as library research or document studies. In this study the authors conducted research on the history of lawThe results of the research conducted by the author are, firstly, it is known that the arrangement of court friends in the criminal justice system is still not specifically regulated where the explanation and procedure for filing a court friend has not been explained in the Criminal Procedure Code and the criminal justice system, people and bodies that have filing a court friend on the basis of the provisions of Article 5 paragraph 1 of Law No. 48 concerning judicial power and if the judge requests it it will be based on the basis of Article 180 paragraph 1 of the Criminal Procedure Code. Furthermore, it is known and applied to the position of court friends in the process of proving a criminal case, even though the court does not yet have clear arrangements regarding the sound of the evidence submitted by court friends both from the law and the Criminal Procedure Code.Keywords: Position-Friends of the Court-Justice System